2021
DOI: 10.3390/math9161839
|View full text |Cite
|
Sign up to set email alerts
|

Q-Learnheuristics: Towards Data-Driven Balanced Metaheuristics

Abstract: One of the central issues that must be resolved for a metaheuristic optimization process to work well is the dilemma of the balance between exploration and exploitation. The metaheuristics (MH) that achieved this balance can be called balanced MH, where a Q-Learning (QL) integration framework was proposed for the selection of metaheuristic operators conducive to this balance, particularly the selection of binarization schemes when a continuous metaheuristic solves binary combinatorial problems. In this work th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 97 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…While some MHs operate on binary domains without a binary scheme, studies have demonstrated that continuous MHs supported by a binary scheme perform exceptionally well on multiple NP-hard combinatorial problems [ 1 ]. Examples of such MHs include the binary bat algorithm [ 28 , 29 ], particle swarm optimization [ 30 ], binary sine cosine algorithm [ 2 , 31 , 32 , 33 ], binary salp swarm algorithm [ 34 , 35 ], binary grey wolf optimizer [ 32 , 36 , 37 ], binary dragonfly algorithm [ 38 , 39 ], the binary whale optimization algorithm [ 2 , 32 , 40 ], and the binary magnetic optimization algorithm [ 41 ].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…While some MHs operate on binary domains without a binary scheme, studies have demonstrated that continuous MHs supported by a binary scheme perform exceptionally well on multiple NP-hard combinatorial problems [ 1 ]. Examples of such MHs include the binary bat algorithm [ 28 , 29 ], particle swarm optimization [ 30 ], binary sine cosine algorithm [ 2 , 31 , 32 , 33 ], binary salp swarm algorithm [ 34 , 35 ], binary grey wolf optimizer [ 32 , 36 , 37 ], binary dragonfly algorithm [ 38 , 39 ], the binary whale optimization algorithm [ 2 , 32 , 40 ], and the binary magnetic optimization algorithm [ 41 ].…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, there are several related works on binarization [ 30 , 42 ] that have laid the groundwork for investigations into this domain problem, as there are several practical applications where working in binary domains is necessary. Moreover, research has emerged on how the change of binarization schemes affects each iteration of the search process, such as time-varying binarization schemes [ 38 ] or binarization scheme selectors [ 2 , 32 , 60 ], where the influence of binarization schemes and their impact at both the problem level and each iteration of the search has been demonstrated.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations